Pengaruh Terapi Bekam Titik Al Warik Terhadap Penurunan Skala Nyeri pada Penderita Low Back Pain di Klinik Holistik Nursing Therapy Probolinggo - Silvia Nur Afkarina; Ro’isah; Iin Aini Isnawati (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Low back pain is still a trigger for health problems that interfere with activities. If not treated properly, it can reduce lumbar mobility so that there is limited movement. There are several treatment strategies for low back pain, namely pharmacology and non-pharmacology. Non-pharmacology therapy that can be done is cupping therapy. The cupping therapy that is carried out is Al Warik point cupping therapy. This study aims to determine the effect of Al Warik point cupping on reducing the pain scale in low back pain sufferers at the Probolinggo holistic nursing therapy clinic. The type of research used a pre-experiment with a one group pre-post test design. The population was 38 low back pain sufferers at the Probolinggo holistic nursing therapy clinic, the sample determination used the accidental sampling technique that met the criteria of 34 respondents. The instrument used the cupping therapy module, data management with the editing, coding, scoring, and tabulating processes. Furthermore, it was analyzed using the Wilcoxon test. The results of this study indicated that the average pain scale value that occurred before cupping therapy at the Al Warik point was 7.00, standard deviation 1.073, and the average pain scale value after cupping therapy at the Al Warik point was 4.74, standard deviation 1.024, the analysis test using the Wilcoxon test showed a decrease in the Low Back Pain Pain Scale at the Holistic Nursing Therapy Clinic in Probolinggo (ρ = 0.000 <α = 0.005). Cupping therapy can be a traditional alternative treatment that can be done routinely for the healing process of low back pain by performing cupping therapy at the Al Warik point.